rezolva ecuatia: 3[3(2x-5)-2(4x-1)]+26=4[4(x+3)-3(x+2)]+13
Răspunsuri la întrebare
Răspuns de
2
3(6x-15-8x+2)+26=4(4x+12-3x-6)+13
3(-2x-13)+26=4(x+6)+13
-6x-39+26=4x+24+13
-6x-13=4x+37
-14=10x+37
10x=37-(-14)
10x=37+14
10x=51
x=5,1
Puncte? :)
3(-2x-13)+26=4(x+6)+13
-6x-39+26=4x+24+13
-6x-13=4x+37
-14=10x+37
10x=37-(-14)
10x=37+14
10x=51
x=5,1
Puncte? :)
Alte întrebări interesante
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă